Difficulties in the differential diagnosis of large solitary pulmonary cysts. (30th October 2021) - Frick, Anna Elisabeth; Ankersmit, Hendrik Jan; Simonitsch-Klupp, Ingrid; Hoetzenecker, Konrad
Abstract: Large solitary cystic lesions are a rare finding, and their differential diagnosis includes cystic airspaces associated with lung cancer, congenital pulmonary airway malformations and pneumatoceles. Here, we report 3 consecutive patients who presented with a large solitary pulmonary cyst on chest computed tomography. All underwent surgical resection, and the histopathological findings were different in all 3 cases. In one patient, a very rare finding of squamous cell carcinoma arising from the cystic lesion in the left lower lobe was confirmed. Therefore, in carefully selected cases, pulmonary cysts should be resected based on the potential risk for recurrent infection and the development of malignancy. Abstract : Pulmonary cysts are thin-walled (<4 mm) gas or fluid-filled structures within the lung parenchyma.